The Binomial Recurrence. Issue 3 (1st June 2016) - Spivey, Michael Z.
Summary: We give a new, direct argument that the solution to the binomial recurrence is the binomial coefficient. Our argument does not assume that the solution is known in advance nor does it rely on anything other than basic properties of two-variable triangular recurrence relations.